Constraining self-interacting fermionic dark matter in admixed neutron stars using multimessenger astronomy - Mariani, Mauro (2024)
We investigate the structure of admixed neutron stars with a regular hadronic component and a fraction of fermionic self-interacting dark matter. Using two limiting equations of state for the dense baryonic interior, constructed from piecewise generalized polytropes, and an asymmetric self-interacting fermionic dark component, we analyse different scenarios of admixed neutron stars depending on the mass of dark fermions mχ, interaction mediators mϕ, and self-interacting strengths g. We find that the contribution of dark matter to the masses and radii of neutron stars leads to tension with mass estimates of the pulsar J0453+1559, the least massive neutron star, and with the constraints coming from the GW170817 event. We discuss the possibilities of constraining dark matter model parameters g and y ≡ mχ/mϕ, using current existing knowledge on neutron star estimations of mass, radius, and tidal deformability, along with the accepted cosmological dark matter freeze-out values and self-interaction cross-section to mass ratio, σSI/mχ, fitted to explain Bullet, Abell, and dwarf galaxy cluster dynamics. By assuming the most restrictive upper limit, σSI/mχ < 0.1 cm2 g−1, along with dark matter freeze-out range values, the allowed g–y region is 0.01 ≲ g ≲ 0.1, with 0.5 ≲ y ≲ 200. For the first time, the combination of updated complementary restrictions is used to set constraints on self-interacting dark matter.